PENGARUH KEPERCAYAAN MEREK TERHADAP LOYALITAS KONSUMEN PADA PENGGUNAAN AIR MINUM KEMASAN ARINDO KOTA KENDARI - Herdiyanto Husain (Universitas Muhammadiyah Kendari, 2017)
This research intent for analysis brand trust influence to loyalitas consumer on pack drinking water user Arindo PT. Aromaqua Segarindo is Kendari’s City. Brand trust in observational it dikonsepsikan as variable as laten that is measurement is gone upon on two (2) dimensions brand trust (brand trust) according to Kotler, examinee via variable reliability (keterandalan is brand) and variable intentionality (yen and intention to buy). Loyalitas is dikonsepsikan consumer as variable as observation. Observaatinal repondet as much 50 person, determined writing. Data collecting is done by use of questionnaire. Each answer item question is measured by use of scale Likert. Result tests hypothesis with level α = 0,05, point out that Fsig’s point (0.000) smaller of α 0,05, so is declared for that brands trusty variable which cover reliability (X1), intentionality (X2) simultan’s ala having for significan to loyalitas consumer (Y) on trusty level 95%. Partially, examination result also points out that reliability’s variable (X1) and intentionality (X2) having for significaan to loyalitas consumer.